2001
DOI: 10.1161/01.atv.21.4.481
|View full text |Cite
|
Sign up to set email alerts
|

HDL and the Inflammatory Response Induced by LDL-Derived Oxidized Phospholipids

Abstract: Abstract-Oxidation of low density lipoprotein (LDL) phospholipids containing arachidonic acid at the sn-2 position occurs when a critical concentration of "seeding molecules" derived from the lipoxygenase pathway is reached in LDL. When this critical concentration is reached, the nonenzymatic oxidation of LDL phospholipids produces a series of biologically active, oxidized phospholipids that mediate the cellular events seen in the developing fatty streak. Normal high density lipoprotein (HDL) contains at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
254
0
19

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 410 publications
(281 citation statements)
references
References 97 publications
8
254
0
19
Order By: Relevance
“…In vitro studies have demonstrated the capacity of PON1 to prevent LDL (and HDL) oxidation by a variety of pro-oxidant factors, including cellinduced LDL oxidation (1,2). Complementary studies have shown that the anti-oxidant activity of PON1 prevents LDL from acquiring a number of pathological characteristics associated with the atherosclerotic process, notably monocyte mobilization and gene activation (3). The PON1 knockout mouse model confirmed that absence of serum PON1 activity increases the level of lipoprotein oxidation, renders LDL more susceptible to oxidation, decreases the anti-oxidant capacity of HDL and leads to more extensive atheroma formation (4,5).…”
Section: Paraoxonase-1 (Pon1)mentioning
confidence: 82%
See 1 more Smart Citation
“…In vitro studies have demonstrated the capacity of PON1 to prevent LDL (and HDL) oxidation by a variety of pro-oxidant factors, including cellinduced LDL oxidation (1,2). Complementary studies have shown that the anti-oxidant activity of PON1 prevents LDL from acquiring a number of pathological characteristics associated with the atherosclerotic process, notably monocyte mobilization and gene activation (3). The PON1 knockout mouse model confirmed that absence of serum PON1 activity increases the level of lipoprotein oxidation, renders LDL more susceptible to oxidation, decreases the anti-oxidant capacity of HDL and leads to more extensive atheroma formation (4,5).…”
Section: Paraoxonase-1 (Pon1)mentioning
confidence: 82%
“…Incidentally, the SR-B1 receptor was detected immunologically in the CHO-hPON1 line. 3 The particular feature of SR-B1 function is to allow bi-directional transfer of hydrophobic molecules between lipoprotein and cell, without internalization of the lipoprotein particle. We hypothesize that PON1 may exploit this mechanism to allow secretion and correct insertion into the HDL complex.…”
Section: Discussionmentioning
confidence: 99%
“…High‐density lipoproteins (HDLs) have systemic anti‐inflammatory and antioxidant properties and limit endothelial dysfunction and damage by attenuating endothelial cell activation and adhesion molecule expression, by activating endothelial nitric oxide synthase, and by promoting endothelial repair 10, 13, 14, 15, 16, 17, 18, 19, 20. In critically ill patients with pneumonia or sepsis, low HDL cholesterol concentrations are associated with multiorgan dysfunction and short‐ and long‐term death 21, 22.…”
mentioning
confidence: 99%
“…On the basis of studies in Xenopus laevis oocytes, Leitinger and colleagues (64) concluded that POVPC and PGPC elicit their cellular responses through binding to different receptors. This adds to earlier indications that the effects of oxidized phospholipids are receptor-mediated.…”
Section: Discussionmentioning
confidence: 99%